2022
DOI: 10.3389/fcimb.2021.811556
|View full text |Cite
|
Sign up to set email alerts
|

Integrated miRNA and mRNA Expression Profiles Reveal Differentially Expressed miR-222a as an Antiviral Factor Against Duck Hepatitis A Virus Type 1 Infection

Abstract: Duck hepatitis A virus 1 (DHAV-1) is a highly contagious etiological agent that causes acute hepatitis in young ducklings. MicroRNAs (miRNAs) play important regulatory roles in response to pathogens. However, the interplay between DHAV-1 infection and miRNAs remains ambiguous. We characterized and compared miRNA and mRNA expression profiles in duck embryo fibroblasts cells (DEFs) infected with DHAV-1. In total, 36 and 96 differentially expressed (DE) miRNAs, and 4110 and 2595 DE mRNAs, were identified at 12 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In this study, the expression of gga-miR-221-3p was greater in the susceptible group than in the resistant group, and in combination with the above findings in humans, we speculated that gga-miR-221-3p has a proinflammatory effect on APEC infection. miR-222a, another highly expressed miRNA in the susceptible group, can act as an antiviral factor against duck hepatitis A virus 1 ( Sui et al., 2022 ). However, few other miRNAs, such as gga-miR-1663-3p, gga-miR-222b-3p, and gga-miR-7, have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression of gga-miR-221-3p was greater in the susceptible group than in the resistant group, and in combination with the above findings in humans, we speculated that gga-miR-221-3p has a proinflammatory effect on APEC infection. miR-222a, another highly expressed miRNA in the susceptible group, can act as an antiviral factor against duck hepatitis A virus 1 ( Sui et al., 2022 ). However, few other miRNAs, such as gga-miR-1663-3p, gga-miR-222b-3p, and gga-miR-7, have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, high-throughput sequencing techniques were used to determine the expression profiles of miRNAs in animals, plants and viruses. Some studies showed that the integrated analysis of miRNA and mRNA in viral infection samples could confirm the regulatory mechanism of miRNA ( 28 30 ). The analysis of giant pandas in captivity vaccinated against CDV was operated with miRNA-mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers utilized lncRNA sequencing and RNA sequencing ( RNA-seq ) to examine genetic alterations in DHAV-1-infected duck embryo fibroblast ( DEF ) cells ( Sui et al, 2022 ). Additionally, a study elucidated mRNA and miRNA profiles in DHAV-1-infected duck embryo fibroblast ( DEF ) cells through RNA-seq and miRNA sequencing ( miRNA-seq ) ( Sui et al, 2021 ). Furthermore, mRNA expression profiles were analyzed in duck liver infected with DHAV-3 ( Cao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%